Penerapan Metode Diskusi Simposium Melalui Keterampilan Bertanya untuk Meningkatkan Hasil Belajar pada Mata Pelajaran Pendidikan Agama Islam Kelas X SMAN 1 Basa Ampek Balai - Hartati, Yeni (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve student learning outcomes in Islamic Religious Education (PAI) by implementing the symposium discussion method through questioning skills. The research was conducted with class X E 2 students at SMAN 1 Basa Ampek Balai using a Classroom Action Research (CAR) design over two cycles. The results revealed a significant improvement in students’ learning outcomes from cycle I to cycle II, with an average score reaching 86.66%. In cycle II, 73.33% of students achieved the "very good" category, while 26.66% fell under the "good" category. The symposium discussion method proved effective in enhancing students’ understanding through active participation and the development of questioning skills. Therefore, this method can be considered an effective alternative for improving learning outcomes in PAI subjects